2019
DOI: 10.1186/s12966-019-0874-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of interventions in the childcare setting with direct parental involvement: effectiveness on child weight status and energy balance-related behaviours

Abstract: BackgroundThe early years are a crucial period to promote healthy energy balance-related behaviours in children and prevent overweight and obesity. The childcare setting is important for health-promoting interventions. Increasingly, attention has been paid to parental involvement in childcare-based interventions. The aim of this systematic review is to evaluate the effectiveness of these interventions with direct parental involvement on the children’s weight status and behavioural outcomes.MethodsA systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 74 publications
1
44
0
Order By: Relevance
“…Contradictory messages in different settings can create confusion for children and may hinder their ability to make healthy lifestyle choices [ 41 ]. Although efforts have been made to engage parents as much as possible in HSSP, more work is needed to understand how best to reach and involve parents, something also highlighted as an important factor for intervention effectiveness in childcare settings [ 42 ], where possible factors could include a firmer structure for home assignment and improve communication between home and school [ 27 , 28 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory messages in different settings can create confusion for children and may hinder their ability to make healthy lifestyle choices [ 41 ]. Although efforts have been made to engage parents as much as possible in HSSP, more work is needed to understand how best to reach and involve parents, something also highlighted as an important factor for intervention effectiveness in childcare settings [ 42 ], where possible factors could include a firmer structure for home assignment and improve communication between home and school [ 27 , 28 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the importance of determinants in different types of environments on physical activity and sedentary behavior [36,61,62]. Systematic reviews have also stressed the importance of integrated interventions, i.e., combining the physical and sociocultural environment [63,64]. The integrated approach taken in SuperFIT, in which these different types of environments were taken into account was expected to be supportive for intervention effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, less than 1/3rd of dietary behavior guidelines recommended some form of parent engagement strategy. Despite mixed evidence surrounding the impact of parent involvement on child diet [ 78 , 79 ], there is some suggestion that involvement of parents particularly around the packing of childcare lunchboxes can improve vegetable intake [ 80 ].…”
Section: Discussionmentioning
confidence: 99%